DEFINITION pr2_gen_sort()
TYPE =
∀c:C.∀x:T.∀n:nat.(pr2 c (TSort n) x)→(eq T x (TSort n))
BODY =
assume c: C
assume x: T
assume n: nat
suppose H: pr2 c (TSort n) x
assume y: T
suppose H0: pr2 c y x
we proceed by induction on H0 to prove (eq T y (TSort n))→(eq T x y)
case pr2_free : :C t1:T t2:T H1:pr0 t1 t2 ⇒
the thesis becomes ∀H2:(eq T t1 (TSort n)).(eq T t2 t1)
suppose H2: eq T t1 (TSort n)
(H3)
we proceed by induction on H2 to prove pr0 (TSort n) t2
case refl_equal : ⇒
the thesis becomes the hypothesis H1
pr0 (TSort n) t2
end of H3
(h1)
by (refl_equal . .)
eq T (TSort n) (TSort n)
end of h1
(h2)
by (pr0_gen_sort . . H3)
eq T t2 (TSort n)
end of h2
by (eq_ind_r . . . h1 . h2)
we proved eq T t2 (TSort n)
by (eq_ind_r . . . previous . H2)
we proved eq T t2 t1
∀H2:(eq T t1 (TSort n)).(eq T t2 t1)
case pr2_delta : c0:C d:C u:T i:nat :getl i c0 (CHead d (Bind Abbr) u) t1:T t2:T H2:pr0 t1 t2 t:T H3:subst0 i u t2 t ⇒
the thesis becomes ∀H4:(eq T t1 (TSort n)).(eq T t t1)
suppose H4: eq T t1 (TSort n)
(H5)
we proceed by induction on H4 to prove pr0 (TSort n) t2
case refl_equal : ⇒
the thesis becomes the hypothesis H2
pr0 (TSort n) t2
end of H5
(H6)
by (pr0_gen_sort . . H5)
we proved eq T t2 (TSort n)
we proceed by induction on the previous result to prove subst0 i u (TSort n) t
case refl_equal : ⇒
the thesis becomes the hypothesis H3
subst0 i u (TSort n) t
end of H6
by (subst0_gen_sort . . . . H6 .)
we proved eq T t (TSort n)
by (eq_ind_r . . . previous . H4)
we proved eq T t t1
∀H4:(eq T t1 (TSort n)).(eq T t t1)
we proved (eq T y (TSort n))→(eq T x y)
we proved ∀y:T.(pr2 c y x)→(eq T y (TSort n))→(eq T x y)
by (insert_eq . . . . previous H)
we proved eq T x (TSort n)
we proved ∀c:C.∀x:T.∀n:nat.(pr2 c (TSort n) x)→(eq T x (TSort n))